(untitled) (Revista de Estudos da Linguagem, 1996)
The aim of this paper is to provide an analysis for the complementary distribution between the Brazilian forms você and cê (Uyou"). I argue that cê is a clitic and constitutes a step in the grammaticalization process of the form Vossa Mercê.